IMPLIKASI KEDUDUKAN AKTA CESSIE TERHADAP OBJEK JAMINAN YANG TELAH MELEWATI MASA BERLAKU - Dharmawan, Rifky Dwi (Fakultas Hukum Universitas Narotama, 2024)
Abstract In civil law, collateral agreements such as cessie deeds are important instruments to protect the interests of the parties in legal transactions. However, when the security object in the cessie deed expires, questions arise about the legal standing of the cessie deed and the rights of the assignee. Fundamental questions include whether the transferred lien is still valid and whether the assignee is still entitled to pursue the lien. The legal implications of this situation are complex, depending on the terms of the cessie agreement and legal principles such as legal certainty and protection of interests. Courts may be faced with the difficult task of interpreting the law and reaching a fair decision. The impact extends to lenders, assignees and debtors, who must understand the legal implications to manage risk and safeguard their interests in cession transactions. Keywords: Cession, Notary, Civil Law